(untitled) (Revista Brasileira de Contabilidade e Gestão, 2013)
A major environmental issue that currently concerns a considerable portion of the population is the excessive solid waste generation, coupled with their inadequate management and destination. In order to relieve this situation was created, by Law 12.305/2010, the Solid Waste National Program, with the aim of encourage cities and states to create projects based on the reduction of these rejects. Besides the government incentive, environmental education may assist this point by deploying healthy environmental habits since the early grades, indirectly covering, parents and community. To check the environmental knowledge level of the educators, a survey was conducted, classified as qualitative and quantitative. The data collection was conducted through questionnaires, consisting in nine open-ended questions and nine closed-ended questions. The questionnaire was applied to the teaching staff of the Orlando Bertoli Basic Education School, in Presidente Getúlio, Santa Catarina, during the second half of October, 2012. As the result of this survey, it is clear that occurred some mistakes and misunderstandings by the professors, probably due the lack of information about solid waste. However, it is possible to perceive a real preoccupation of teachers about the environmental education, indicating and emphasizing the role of educators and educational institutions in the formation of conscious citizens.